2023
DOI: 10.1177/20563051231177921
|View full text |Cite
|
Sign up to set email alerts
|

Issue Communication Network Dynamics in Connective Action: The Role of Non-Political Influencers and Regular Users

Abstract: Social media influencers (SMIs) have prevailed in online communication networks and can play key roles in connective action. However, how influencers connectively drive activism communication network is less clear. This study conceptualizes issue influencers as users who emerge as influential nodes in shaping the communication network in a contentious political issue niche. A new typology of influencers is proposed based on both issue and platform influence. Drawing on connective action theory and SMI studies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Yet in this case, the influencer demonstrates their shared identity with their followers to manipulate their political opinion. They perform authenticity (Abidin, 2015;Abidin & Ots, 2016;Abidin & Thompson, 2012;Banet-Weiser, 2012Duffy, 2017;McQuarrie et al, 2013) to enhance their credibility with marginalized communities and the potential political impact of their messaging (Goodwin et al, 2023;Ma & Zhang, 2022;Mirbabaie et al, 2021;Schmuck et al, 2022;Stewart et al, 2023;Tang, 2023). Rather than forcing members of marginalized groups to "authenticate" themselves (Reddi et al, 2021), they authenticate their own position in the marginalized community expressly for the purpose of manipulating opinion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet in this case, the influencer demonstrates their shared identity with their followers to manipulate their political opinion. They perform authenticity (Abidin, 2015;Abidin & Ots, 2016;Abidin & Thompson, 2012;Banet-Weiser, 2012Duffy, 2017;McQuarrie et al, 2013) to enhance their credibility with marginalized communities and the potential political impact of their messaging (Goodwin et al, 2023;Ma & Zhang, 2022;Mirbabaie et al, 2021;Schmuck et al, 2022;Stewart et al, 2023;Tang, 2023). Rather than forcing members of marginalized groups to "authenticate" themselves (Reddi et al, 2021), they authenticate their own position in the marginalized community expressly for the purpose of manipulating opinion.…”
Section: Discussionmentioning
confidence: 99%
“…The logic behind these choices is that "these regular people have more intimate, local connections" and their messaging will "hit harder" (Woolley, 2023, p. 88). Studies in various contexts have shown that social media influencers, political and otherwise, can increase their followers' interest in politics (Schmuck et al, 2022), shape discourse on political issues (Tang, 2023), and act as catalysts in connective action movements (Ma & Zhang, 2022;Mirbabaie et al, 2021). This gives credence to the power of political and social micro-or nanoinfluencers within intimate, smaller, and highly connected social media spaces.…”
Section: Influencing Politicsmentioning
confidence: 99%
“…Finally, Tang (2023) investigates digital connective action in response to a controversial policy issued by the Chinese Communist Party, which targets the expression of effeminate gender aesthetics among men. By examining how a contentious political issue such as the new policy is discussed by Weibo users, the author demonstrates that who becomes an influencer remains in flux and is issue-specific as well as platform-specific.…”
Section: Political Influencer Scholarship and Contributions In This S...mentioning
confidence: 99%